The concept of angst in Nokolai Gogol's "The Nose" - Abu Jweid, Abdalhadi Nimer Abdalqader; Ali Termizi, Arbaayah (American Research Institute for Policy Development, 2014)
This paper explores the insights that philosophy can bring to administrative and bureaucratic critique, focusing on the work of Nikolai Gogol's "The Nose". It examines the ways in which Gogol's "The Nose" represents the concept of angst in order to satirize the Russian social and religious status. This paper reads "The Nose" as a text very much of its time. It moves into fantastic themes and is a project involving recovering social histories, thus becoming a key example of the productive coalescence of society and religion amidst early nineteenth-century concerns. Gogol's satire of society presages many subsequent social religious analyses, presenting a severe indictment of society as a rigid and impersonal state machine resulting in meaninglessness, absurdity and tragedy. It encompasses the institutional level and fundamental ruptures in society caused by a surfeit of religion, as depicted in "The Nose". On a more philosophical level, "The Nose" explores the effects of society on the individual, portraying the alienation, futile activity and servility inflicted on lower-level functionaries through various problems, such as the loss of identity, the absence of meaningful existence and a lack of integration between public and private lives.